2014
DOI: 10.5539/ijms.v6n1p155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ambient Scents on Consumer Responses: Consumer Type and His Accompaniment State as Moderating Variables

Abstract: The aim of this research is to study the effect of ambient scents on consumers' responses and in particular the moderating effect of consumer type (hedonic vs utilitarian) and his accompaniment state (accompanied vs single).An experiment was conducted in a real business context (NIKE store), where 400 customers were surveyed. The results indicate that a pleasant ambient scent improves evaluation of store environment, products, quality of services provided, the level of pleasure experienced, the level of stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(27 reference statements)
1
9
0
2
Order By: Relevance
“…Ambient conditions in fitness centers were evidenced to be a significant predictor of customer intentions to spread positive word of mouth and to renew their membership with the fitness center in the future. This is in line with the findings of previous empirical studies (Bouzaabia, 2014;Lim, et al, 2020;Shashikala & Suresh, 2013). Ong and Yap (2017) for instance, found individual behavioral intentions to be significantly affected by the physical dimension including ambient factors of the servicescape.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ambient conditions in fitness centers were evidenced to be a significant predictor of customer intentions to spread positive word of mouth and to renew their membership with the fitness center in the future. This is in line with the findings of previous empirical studies (Bouzaabia, 2014;Lim, et al, 2020;Shashikala & Suresh, 2013). Ong and Yap (2017) for instance, found individual behavioral intentions to be significantly affected by the physical dimension including ambient factors of the servicescape.…”
Section: Discussionsupporting
confidence: 92%
“…Ong and Yap (2017) for instance, found individual behavioral intentions to be significantly affected by the physical dimension including ambient factors of the servicescape. Likewise, the findings of Bouzaabia (2014) indicated that customers show greater revisit intentions for stores with pleasant ambient scents. Ambient conditions were also reported as a critical determinant of customer loyalty (Shashikala & Suresh, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…The higher the level of satisfaction among shoppers, the greater the intension of revisiting. Therefore, consumption always has a positive sign for shopping malls [79].…”
Section: Entertainment and Consumptionmentioning
confidence: 96%
“…Alpert ve diğerleri ( 2005), müziğin ürünler üzerinde sembolik anlamlar ve duygular çağrıştırması nedeniyle tüketici satın alma davranışlarını etkilediği sonucuna varmışlardır. Bouzaabia (2014), güçlü bir ikna edici olan hoş bir ortam kokusunun ürünlerin, sunulan hizmetlerin kalitesini, deneyimlenen zevk düzeyini, mağaza algısını ve müşterilerin satın alma niyetlerini iyileştirdiğini ortaya koymuştur. Klatzky ve Peck (2012), ürün özelliklerinin dokunmaya elverişli olduğu durumlarda, dokunma ihtiyacı sayesinde müşterilerin tüketim motivasyonlarının buna yönelik olarak etkilendiğini belirlemiştir.…”
Section: Duyusal Markalamaunclassified